The Historical and Present-Day Role of Non-Governmental Organisations before the Inter-American Human Rights System in Documenting Serious Human Rights Violations and Protecting Human Rights and the Rule of Law Through Ensuring Accountability - Clara Burbano Herrera (Utrecht University School of Law, 2021)
From a Latin-American perspective, even in a context where the rule of law has been under attack or has been very weak, the role of human rights NGOs has been and is very relevant in terms of documenting human rights violations, and seeking and bringing justice for the victims of those violations, as well as acting as a guardian angel to the Inter-American human rights system. The role of NGOs within the Inter-American human rights system has to be understood taking into account the specific political and the legal-normative context on the continent. Indeed, the role played by human rights NGOs in the Americas has responded/responds to the political reality of repressive regimes and present-day fragile democracies struggling to uphold human rights and rule of law standards. Furthermore, the legal-normative context, i.e. the American Convention on Human Rights and the interpretation given by the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights to its provisions, has also given and gives NGOs ample space to interact through different methods and strategies in a less active to a very active manner with the human rights monitoring bodies from 1959 on.